Mass production of LiAl alloys by the step-controlled casting process. (5th June 2016) - Tsai, Yu-Chou; Lee, Sheng-Long; Lin, Chih-Kuang; Suwandi, Anita
Abstract: An innovative method, step-controlled casting process (SCCP), was developed to produce LiAl alloy in mass production, which was potential for hydrogen storage. Formerly, the large difference in melting points between Li and Al was considered as a disadvantage to produce LiAl alloy. However, this disadvantage was overcome by SCCP. Characterization of as-cast specimens were performed using X-ray diffraction (XRD), inductively coupled plasma-atomic emission spectroscopy (ICP-AES), optical microscopy (OM), revealing that single phase LiAl alloy was successfully fabricated by SCCP with 94% yield. The hydrogen storage properties were also investigated by temperature-programmed decomposition (TPD) and XRD. The highest maximum hydrogen storage capacity reached 2.4 wt.% of the ball milled LiAl alloy when hydrogenated under 65 atm at 400 °C. Graphical abstract: Highlights: High purity LiAl alloys were successfully obtained by the step-controlled casting process (SCCP). The fabricated LiAl alloy has potential for hydrogen storage. Hydrogen storage properties were enhanced by ball milling.